Multilingualism in Film (Peter Lang International Academic Publishers, 2024)
Multilingualism is a phenomenon that has become increasingly visible in popular cinema and thus is currently a very novel object of academic inquiry. The present volume is a cutting-edge collection of cross- and transdisciplinary takes on this phenomenon and its different aspects. Its topics range from translation theory to political and aesthetic quandaries of audiovisual translation and subtitling, to narratological function of multilingualism in fiction, to language ideologies and language poetics onscreen. Its authorship is a worldwide body of perspectives, whose contributions span a distinctive collection of international, national and regional film traditions.